A Complicated Pregnancy : Whether Mary was a Virgin and Why It Matters - Roberts, Kyle A. (Book collections on Project MUSE., 2018)
The virgin birth is a much-loved story in the Christian tradition. It is the standard "origin story" of Jesus, marking the incarnation of the Son of God. Today, however, many theologians dispute the tradition of the virginal conception on both historical and scientific grounds. As a progressive Protestant theologian--and a husband and a father--Kyle Roberts was growing unsure of his belief in Mary's virginity. It contradicted modern science, and it seemed to undermine her feminine power. So he set out to investigate the virgin birth from every angle: the Bible, history, science, and philosophy. A Complicated Pregnancy records his journey through the evidence and the myth. Did the Holy Spirit form Jesus as a zygote in Mary's womb? If so, where did Jesus get his male genome? Was Jesus's birth really bloodless, as the early church believed, and is Mary a "perpetual virgin"? Roberts's quest is a fascinating journey through history, biblical interpretation, and church politics. His conclusion surprised him, and it will surprise you, too.